ANALISIS KECEMASAN PADA IBU HAMIL DALAM MENGHADAPI PERSALINAN DI MASA PANDEMI COVID-19 DI RUMAH SAKIT IMELDA MEDAN - Khairani; Puput Melati Hutauruk (Jurnal Ilmiah Kebidanan Imelda, 2022)
Pregnant women are one of the groups that are vulnerable to the risk of transmitting Covid-19, this happens because pregnant women tend to experience physical changes that can lower their immune system, if the immune system decreases, the Covid-19 virus will easily enter and cause pregnant women was infected with the Covid-19 virus. Pregnancy during a pandemic like this may be a risk factor for anxiety disorders in pregnant women. Pregnant women easily experience feelings of worry about something that will happen to them and their children so that it can interfere with mental health in this case anxiety disorders. These negative feelings are increasing during the current Covid-19 pandemic. This feeling of anxiety is characterized by worrying about being ignored or isolated. There is a relationship between education and anxiety for pregnant women at Imleda Hospital Medan with p-value 0.002 < =0.05 and there is a relationship between parity and anxiety for pregnant women at Imelda Hospital Medan with p-value 0.001 < =0.05 Closeness between parity and Anxiety at Imelda Hospital Medan is in the strong category